Development of Evaluation and Self-Reflection Instruments for Diagnosing Teacher Candidate Competencies in Microteaching Courses - Agus Maramba Meha; Daniel Frengky Kamengko; Theodora S.N Manu; Norcy Beeh (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study addresses the limited availability of validated diagnostic instruments for assessing teacher candidate competencies in microteaching courses, a gap that has resulted in inconsistent evaluation practices and weak competency identification. In many teacher education programs, microteaching assessments still rely on informal observations and subjective judgments, which limits the accuracy of competency diagnosis and weakens feedback for professional development. The absence of standardized and validated diagnostic tools has made it difficult to systematically identify specific strengths and weaknesses of teacher candidates. The research aimed to develop an evaluation and self-reflection instrument covering four key teacher competencies: pedagogical, professional, personality, and social. Using the ADDIE development model, the instrument was designed, validated by expert reviewers, and tested with Biology Education students in their microteaching course. Validation processes confirmed high feasibility across design, content, and language aspects. User testing with students and lecturers also indicated strong acceptability and practical relevance. The resulting instrument provides a structured and multi-dimensional framework for diagnosing competency strengths and weaknesses, offering more systematic support for improving teacher candidate performance in microteaching settings.